LEGISLATIVE BASE OF PREPORATION OF THE FUTURE EDUCATORS FOR THE CHARITABLE ACTIVITY IN UKRAINE (90s of the 20th century – the beginning of the 21st century) - Kvas, Olena; Ternopilska, Valentina (Mountain School of Ukrainian Carpaty, 2023)
The article is devoted to the normative and legal background of training future teachers for charitable activities in Ukraine (90s of the XXth century - the beginning of the XXIst century). He Law of the Ukrainian SSR «On Education» (1991) was analyzed; the Law of Ukraine «About the charitable activity and charitable organisations» (2012). «State national program «Education» («Ukraine of the XXIst century») (1993), «National Doctrine of Education Development», Laws of Ukraine («On Vocational and Technical Education» (2012), «About higher education» (2014), «About Education» (2017), «About complete general secondary education»(2020)); The National Strategy for the Development of the Education System in Ukraine for 2012-2021, Concept of development of pedagogical education (2018); The order of the Ministry of Education and Science of Ukraine «On approval of the Regulation on the certification of teaching staff» (2022). The main provisions of the Pedagogical Constitution of Europe (2013) are analyzed, which are based on important axiological components related to the orientation of the educational process in higher education institutions to achieve the highest moral and spiritual development, and the potential opportunities of individuals, determined by the assimilation of universal and national values; consist in ensuring the psychological and pedagogical conditions for the identification, development and realization of cognitive independence and meaningful and creative self-activity of the individual, his formation as the creator of his own life, capable of prognostically making a conscious choice and being responsible for actions, deeds, as well as adequately, mobilized and competently responding to changes , life's challenges and constantly self-improvement and success, namely: basic pedagogical values (tolerance, democracy, peace, environmental safety, human rights and solidarity, mercy and conscience, responsibility); the main tasks of teacher training (forming the ability for practical educational activities as a dynamic combination of ethical values and cognitive, metacognitive, interpersonal and practical abilities and skills, knowledge and understanding); the main competencies of the individual, which are outlined not only by awareness, but also by the level of intelligence, will, abilities, values, etc.; the main strategies of the successful activity of the teacher, among which: authenticity, originality, visualization of knowledge, democracy, dialogicity, research, integrativeness, constructivism, leadership, personal orientation, consistency, reflexivity, ability to develop, social orientation, reliance on relevant experience, cooperation, purposefulness; axiological component of practical training of future teachers; academic mobility, which contributes to the formation of cross-cultural values, tolerance and willingness to cooperate.